Evidence on unclaimed charitable contributions from the Introduction of third-part information reporting in Denmark - Christian Gillitzer; Peer Ebbesen Skov (University of Copenhagen, Economic Policy Research Unit (EPRU), 2013)
The introduction of information reporting and pre-population of charitable tax deductions in Denmark in 2008 coincided with a doubling in the number of tax deductions claimed, and a 15 percent rise in the value of claims. We attribute this change to incomplete claiming of eliglbe charitable tax deductions under the prior self-reporting regime: a pre-form randomized audit shows a neglible amount of chaitable overreporting, and we present evidence that there was no change in giving behavior aorund the time of the reform. We estimate that pre-year average amount of forgone tax benefits to be small, but find that many tax-payers repeatedly failed to claim eligble charitable tax deductions under the self-reporting regime. We provide evidence on information frictions from taxpayer behavior due to a notched subsidy scheme.
Keywords: 330; Steuervergünstigung; Einkommensteuer; Gemeinnützige Organisation; Dänemark